Experimental and Clinicolaboratory Evaluation of Complex Therapy Efficacy in Arboviral Infections - M. G. Romatsov; Kh. M. Galimzyanov; O. M. Lokteva; A. L. Kovalenko; A. V. Stepanov (Антибиотики и Химиотерапия)
Search for drugs efficient in prophylaxis and treatment of dangerous infections (especially arboviral ones) is rather actual, since no specific therapy is available. Many-year investigations of interferon inductors showed that they had immunomodulating, antiviral and antiinflammatory effects and were low toxic. The present study demonstrated that the protective effect was the following: Venezuelan equine encephalitis (VEE) - cycloferon > amixin = ridostin, Rift Valley fever (RVF) - cycloferon > amixin > ridostin, predator pox (PP) - cycloferon > amixin = ridostin, that was obvious that cycloferon was the most active agent in the treatment of VEE, RVF and PP, thus making it possible to acknowledge its priority in prophylaxis and therapy of dangerous viral infections (DVI). Ribavirin in combination with cycloferon solution or cycloferon tablets provided shorter periods of the fever, minimized the intoxication syndrome, promoted earlier resolution of hemorrhagic eruption and lowered the frequency of complications, which was in favour of the disease prognosis.